Pengaruh Pola Tidur Terhadap Konsentrasi Dan Performa Akademik Mahasiswa Fakultas Ilmu Tarbiyah Uin Raden Mas Said Surakarta - Marhenisaputri, Intan (CV. SINAR HOWUHOWU, 2025)
Sleep is a vital physiological need that plays an essential role in supporting students' concentration and academic performance. This study aims to analyze the relationship between sleep quality and student concentration levels, considering additional factors such as stress and study habits. A quantitative approach was employed using an online survey distributed to 21 students from the Faculty of Tarbiyah at UIN Raden Mas Said Surakarta. Data were collected through a questionnaire covering aspects such as sleep duration and patterns, napping habits, and factors affecting sleep quality. The results indicate that most students sleep 6–7 hours per night and usually go to bed between 10:00 PM and midnight, aligning with general health recommendations. However, a portion of students reported insufficient sleep and sleep disturbances due to academic workload, gadget use, and stress. Irregular napping habits and excessively long naps were also found to disrupt nighttime sleep patterns. The study concludes that poor sleep quality and irregular sleep patterns can negatively impact students’ concentration and academic performance. Therefore, time management, limited gadget use before bedtime, and institutional support are essential to help students maintain healthy sleep habits.